Cost analysis and efficiency of sub-district health facilities in two districts in ghana - Aboagye, A.Q.; Degboe, A.N. (My University, 2011)
To establish the full costs borne by sub-district health facilities in providing services, we analysed the costs and revenues of 10 sub-district health facilities located in two districts in Ghana. The full costs were obtained by considering staff costs, cost of utilities, cost of using health facility equipment, cost of non-drug consumables, equipment maintenance expenses, amounts spent on training, community information sessions and other outreach activities as well as all other costs incurred in running the facilities. We found that (i) a large proportion of sub-district health facility costs is made up of staff salaries; (ii) at all facilities, internally generated funds (IGFs) are substantially lower than costs incurred in running the facilities; (iii) average IGF is several times higher in one district than the other; (iv) wide variations exist in efficiency indicators and (v) there is some evidence that sub-district health facilities may not necessarily be financially more efficient than hospitals in using financial resources. We suggest that the study should be replicated in other districts; but in the mean time, the health authorities should take note of the conclusions and recommendations of this study. Efforts should also be made to improve record keeping at these facilities.